In good company - "Cohen, Donald J." (Boston, 2001)
Knowledge has always resided in organizations but it wasn't until the Information Age put a premium on ideas that intellectual capital was recognized as a critical resource. Now, forces like technology, globalization, and the rise of free agency and virtual workplaces are bringing another form of 'hidden' capital to the forefront. "In Good Company" is the first book to examine the role that social capital, a company's 'stock' of human connections such as trust, personal networks, and a sense of community, plays in thriving organizations. Written by leading knowledge management experts Don Cohen and Laurence Prusak, this groundbreaking book argues that social capital is so integral to business life that without it, cooperative action and consequently productive work isn't possible. The authors help today's leaders understand the nature and value of social capital, suggest ways they can encourage and enhance it, and explore how they can protect this vital but increasingly vulnerable resource in a volatile, virtual world. Drawing on major social and economic theories, and the experiences of organizations including the World Bank, Aventis Pharma, Alcoa, Russell Reynolds, and UPS, "In Good Company" identifies the social elements that contribute to knowledge sharing, innovation, and high productivity. The authors convincingly show how almost every managerial decision from hiring, firing, and promotion to implementing new technologies to designing office space is an opportunity for social capital investment or loss. They also reveal the benefits that derive from investments in social capital, such as greater commitment and cooperation, increased talent retention, and more intelligent responses to customer needs.
Keywords: Organisational behaviour